"Ethics is part of that as well": Navigating the landscape of humanitarian healthcare policy - Gillespie, Leigh-Anne (My University, 2017)
In the past decade, there has been a rise in the need for global humanitarian assistance with natural disasters and complex emergencies increasing in severity. Ethical tensions are extensive in humanitarian situations, as aid workers find themselves in unfamiliar and unstable contexts making difficult decisions about right and wrong courses of action. These ethical tensions have repercussions for the people targeted for care and result in moral distress of aid workers. In this dissertation, I seek to highlight new ways of understanding how aid agency policies and agendas contribute to these ethical tensions and clarify their development, implementation, and evaluation in humanitarian settings. In order to understand the policy landscape and provide greater conceptual clarity, the first study in this dissertation identifies and explores the characteristics of policy. The analysis uncovers multiple interpretations of policy and related concepts such as code, guideline, and strategy. In the second study, through a series of semi-structured interviews with individuals working within international humanitarian healthcare organizations (organizational members), a qualitative descriptive analysis reveals how policy is developed, implemented, and evaluated. Findings demonstrate that the realities of humanitarian aid work can differ from the expectations that inform policy, with various social and political factors affecting the policy process. The third study unpacks the ethical tensions arising from policies through an interpretive descriptive approach, with three main themes identified: tensions related to institutional memory loss; clashing departmental priorities; and, social norms and expectations. Results from all three studies help establish a common policy language; identify influences shaping policy development, implementation, and evaluation; and, shed light on the ethical tensions shaped by policy. Together, these findings may be used to help identify new ways to improve policy processes and resolve or better anticipate some of the ethical tensions aid workers may encounter in the course of their work, thereby diminishing moral distress and ultimately benefiting communities that are targeted for care.